Equality speaks : challenges for a fair society. - Catalyst Australia ([Sydney] : Catalyst Australia, 2009)
"Australia may have dodged the bullet that has put the US, Britain and most European economies on life support, but our new collection of essays shows that ? despite our enviable economic position ? Australia is not the egalitarian paradise that many believe it to be. Equality Speaks features an eclectic mix of writers who highlight a common challenge ? to use our (relatively) stable economic times to make the shift to a fairer Australia. It includes new research on the distribution of wealth in Australia. And it brings together some of our sharpest minds to look at paths to a more equal Australia in areas like transport, homelessness, education, women, tax, refugees, work and employment amongst others. This is a great resource for anyone with an interest in social policy and a concern about justice for our communities."--Publisher's web site.
Keywords: Equality -- Australia; Australia -- Social conditions -- 2001-; Australia -- Social policy